High-compaction coated modified lithium manganese iron phosphate positive electrode material as well as preparation method and application thereof
Modifying lithium manganese iron phosphate positive electrode material through nanoification, ion doping, carbon coating and high compaction coating has solved the problems of low conductivity, low density and poor circulation performance, and achieved higher compaction density and circulation stability.
Patent Information
- Application Number
- CN202411812165.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-14
AI Technical Summary
Lithium manganese iron phosphate positive electrode materials have problems such as low electron conductivity, excessive specific surface area, low compaction density, and poor dissolution and high-temperature cycling performance of trivalent manganese ions.
Lithium manganese phosphate is modified through nano-domainization, ion doping, carbon coating and high-compression coating. The crystal structure is improved by multiple element doping and tungsten boride coating, inhibiting the ginger Taylor effect, and improving the compaction density through three-stage grinding.
The compaction density and circulation capacity of lithium manganese iron phosphate are significantly improved, the Mn2+ dissolution and polarization are suppressed, and its stability under high-rate charging and discharge conditions is improved.
Smart Images

Figure CN119627080A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of lithium ion battery materials, and in particular to a high-density coated modified lithium manganese iron phosphate positive electrode material, and a preparation method and application thereof. Background Art
[0002] The disadvantage of poor electronic conductivity of lithium iron phosphate has been significantly improved by nano-scaling, coating with carbon layers and doping with other metal ions, making it successfully commercialized. Lithium manganese phosphate with the same structure has similar specific capacity, but its charge and discharge potential is higher at about 4.1V, so its energy density is 20% higher than that of lithium iron phosphate. However, compared with lithium iron phosphate, lithium manganese iron phosphate has lower conductivity and slower lithium ion diffusion rate, resulting in poorer discharge capacity and rate capability.
[0003] Partial Fe 2+ ions replace Mn 2+ The position of ions in the crystal structure of lithium manganese phosphate, synthesizing lithium iron manganese phosphate, not only enhances the electronic activity, but also maintains the original capacity, making the crystal structure more stable. In theory, lithium iron manganese phosphate can combine the advantages of lithium iron phosphate and lithium manganese phosphate, and is generally considered to be the next generation of olivine-type positive electrode materials. However, lithium iron manganese phosphate has low electronic conductivity and high specific surface area, resulting in poor mass production and processing performance, as well as the dissolution of trivalent manganese ions, low compaction density, and poor high-temperature cycle performance.
[0004] To address the above problems, lithium iron manganese phosphate is modified by nano-forming, ion doping, carbon coating and other methods. For example, Chinese patent CN117049495A discloses a method for preparing a high-conductivity superionic conductor composite lithium iron manganese phosphate positive electrode material, in which a superionic conductor ceramic solid electrolyte (Nasicon type LATP solid electrolyte) and lithium iron manganese phosphate are mixed, and a composite lithium iron manganese phosphate positive electrode material is prepared by a solid phase sintering method. The superconducting ion conductor material can improve the conductivity of lithium iron manganese phosphate and enhance its stability. The synthesis method of this invention patent adopts a solid phase synthesis process to facilitate mass production, but it does not explain the relevant scheme for improving the compaction density.
[0005] Chinese patent CN116812898A discloses a method for preparing a lithium manganese iron phosphate positive electrode material, wherein phosphorus, manganese and iron sources are added to a solvent in a stoichiometric ratio and uniformly mixed, lithium source and carbon source precursors are added for coarse grinding, spray granulation, and high-temperature sintering to obtain a lithium manganese iron phosphate positive electrode material. The purpose of this invention patent is to verify the influence of different manganese contents on the electrochemical curve, and a smooth electrochemical curve is formed when the manganese content is 1-5%. Summary of the invention
[0006] The purpose of the present invention is to provide a high-compacted coated modified lithium iron manganese phosphate positive electrode material and its preparation method and application. The present invention designs multiple element doping and tungsten boride coating to synergistically improve the crystal structure of stable lithium iron manganese phosphate and inhibit the Jan-Taylor effect. In order to improve the compaction density, a three-stage grinding method is adopted, and the coarsely ground, coarse-finely ground, and finely ground slurries are driven into a premixing tank according to different ratios, and the slurries are mixed evenly, thereby achieving grading of different particle sizes to improve the compaction density. Compared with adjusting the particle grading through air flow mill crushing, the mixing degree in the solution system is more uniform.
[0007] In order to achieve the above-mentioned purpose, the present invention adopts the following technical solutions:
[0008] The present invention first provides a high-density coated modified lithium manganese iron phosphate positive electrode material, comprising a doped lithium manganese iron phosphate material and a coating layer;
[0009] The chemical formula of the doped lithium manganese iron phosphate material is Li a Fe b Mn c Mg d Ti e Co f PO4, where 0.9≤a≤1.6, 0.1≤b≤0.9, 0.1≤c≤0.9, 0.01≤d≤0.4, 0.01≤e≤0.4, 0.01≤f≤0.4, b+c+d+e+f=1, a:(b+c+d+e+f)=(0.8~1.3):1;
[0010] The coating layer is tungsten diboride.
[0011] Preferably, the total mass of the high-density compacted and coated modified lithium manganese iron phosphate positive electrode material is 100%, the mass content of tungsten diboride in the coating layer is 0.01%-2.0%, and the mass content of the carbon coating is 1%-10%.
[0012] The present invention also provides a method for preparing a high-density compacted and coated modified lithium manganese iron phosphate positive electrode material, comprising the following steps:
[0013] Step 1: uniformly mix the phosphorus source, iron source, manganese source, lithium source, carbon source, titanium source, magnesium source, cobalt source and dispersant, grind, spray dry and perform a sintering to obtain a semi-finished product of lithium manganese iron phosphate;
[0014] Step 2: The lithium iron phosphate semi-finished product obtained in step 1 is mixed with tungsten boride and sand milling solvent and then subjected to three-stage grinding. The slurries of different particle sizes are batch mixed. After mixing evenly, secondary spray granulation is performed. After secondary sintering, air flow crushing is performed. After screening and demagnetization, a high-density coated modified lithium iron phosphate positive electrode material is obtained.
[0015] Preferably, the phosphorus source in step 1 comprises phosphate, phosphoric acid or ammonium dihydrogen phosphate;
[0016] Iron sources include iron phosphate or iron oxide;
[0017] Manganese sources include manganese dioxide, manganese carbonate, manganese tetraoxide or ferromanganese phosphate;
[0018] The lithium source includes lithium phosphate, lithium hydroxide, lithium dihydrogen phosphate or lithium acetate;
[0019] The titanium source includes titanium oxide, titanium sulfate or titanium chloride;
[0020] Magnesium sources include magnesium nitrate, magnesium chloride, magnesium carbonate or magnesium oxide;
[0021] The cobalt source includes cobalt oxide, cobalt nitrate, cobalt carbonate, cobalt sulfate, cobalt chloride, cobalt bromide, cobalt phosphate or cobalt hydroxide;
[0022] Carbon sources include polypyrrole, sucrose, polyethylene glycol, glucose, polyethylene or polyvinyl pyrrolidone.
[0023] Preferably, the grinding in step 1 is wet grinding, the solvent used includes deionized water, ethanol or methanol, the solid content of the wet grinding is 30-48%, and the grinding medium filling rate is 80%-90%.
[0024] Preferably, the spray drying temperature in step 1 is 100-300° C., the primary sintering temperature is 600-850° C., the sintering time is 8-18 hours, and the sintering atmosphere is an inert atmosphere.
[0025] Preferably, the three-stage grinding described in step 2 is divided into coarse grinding, coarse-fine grinding and fine grinding, wherein the diameter of the coarse grinding medium is 1.2mm-2.0mm; the diameter of the coarse-fine grinding medium is 0.4-1.0mm; the diameter of the fine grinding medium is 0.2-0.4mm; the grinding medium includes agate balls or zirconium balls, etc.
[0026] Preferably, the slurries of different particle sizes described in step 2 are batch mixed and measured by volume ratio, and the sum of the volume ratios of the coarsely ground slurry, the coarsely and finely ground slurry, and the finely ground slurry is 1, wherein the volume ratio of the coarsely ground slurry is 0.1-0.3, the volume ratio of the coarsely and finely ground slurry is 0.2-0.5, and the volume ratio of the finely ground slurry is 0.3-0.9.
[0027] Preferably, the spray drying temperature in step 2 is 100-300° C., the secondary sintering temperature is 600-850° C., the sintering time is 7-16 hours, and the sintering atmosphere is an inert atmosphere.
[0028] The present invention also provides the use of the high-density coated modified lithium manganese iron phosphate positive electrode material in a lithium ion battery.
[0029] Beneficial Effects of the Invention
[0030] 1. The present invention provides a new process of secondary sand grinding and secondary sintering to improve the compaction density of lithium iron manganese phosphate. In the secondary sand grinding process, coarse grinding, coarse-fine grinding and fine grinding are used to grade slurries of different particle sizes. Compared with the traditional powder material grading process, the mixing degree is more uniform, and the grading of different particle sizes can significantly improve the compaction density of the powder.
[0031] 2. The present invention introduces tungsten boride to coat the modified lithium manganese iron phosphate positive electrode material to improve the cycle capacity. After the tungsten boride is coated with the lithium manganese iron phosphate, a chemical force is formed on the surface to effectively inhibit the Mn 2+ Dissolution, significantly imprinting the Jan-Taylor effect, reducing battery polarization, and the positive electrode material can still exhibit good cycle stability even under high-rate charge and discharge conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] In order to make the content of the present invention more clearly understood, the present invention is further described in detail below according to specific embodiments of the present invention in conjunction with the accompanying drawings, wherein:
[0033] Figure 1 It is a schematic diagram of the process route of the present invention.
[0034] Figure 2 This is the charge and discharge curve of the positive electrode material obtained in Example 5 of the present invention.
[0035] Figure 3 This is a SEM image of the positive electrode material obtained in Example 5 of the present invention.
[0036] Figure 4 This is a charge cycle trend diagram of the positive electrode material obtained in Example 5 of the present invention under 1C charge and discharge conditions. DETAILED DESCRIPTION
[0037] The present invention first provides a high-density coated modified lithium manganese iron phosphate positive electrode material, comprising a doped lithium manganese iron phosphate material and a coating layer;
[0038] The chemical formula of the doped lithium manganese iron phosphate material is Li a Fe b Mn c Mg d Ti e Co fPO4, wherein 0.9≤a≤1.6, preferably 1.03, 1.04, 1.05 or 1.06; 0.1≤b≤0.9, preferably 0.37, 0.39, 0.40 or 0.42; 0.1≤c≤0.9, preferably 0.58, 0.59 or 0.62; 0.01≤d≤0.4, preferably 0.02, 0.03 or 0.04; 0.01≤e≤0.4, preferably 0.01, 0.02 or 0.03; 0.01≤f≤0.4, preferably 0.01, 0.02 or 0.03; b+c+d+e+f=1, a:(b+c+d+e+f)=(0.8-1.3):1, preferably (1.01-1.06):1;
[0039] The coating layer is tungsten diboride, and the chemical formula is WB 2 , wherein 0.1 μm<D50<5 μm, and the preferred particle size is 0.1 μm<D50<0.3 μm.
[0040] The total mass of the high-pressure compacted and coated modified lithium manganese iron phosphate positive electrode material described in the present invention is 100%, and the mass content of tungsten boride in the coating layer is preferably 0.01%-2.0%, more preferably 0.07%, 0.1%, 0.2% or 0.3%; the mass content of the carbon coating is preferably 1%-10%, more preferably 1%, 2%, 3% or 4%.
[0041] The present invention also provides a method for preparing a high-density compacted and coated modified lithium manganese iron phosphate positive electrode material, comprising the following steps:
[0042] Step 1: uniformly mix the phosphorus source, iron source, manganese source, lithium source, carbon source, titanium source, magnesium source, cobalt source and dispersant, grind, spray dry and perform a sintering to obtain a semi-finished product of lithium manganese iron phosphate;
[0043] Step 2: The lithium iron phosphate semi-finished product obtained in step 1 is mixed with tungsten boride and sand milling solvent and then subjected to three-stage grinding. The slurries of different particle sizes are batch mixed. After mixing evenly, secondary spray granulation is performed. After secondary sintering, air flow crushing is performed. After screening and demagnetization, a high-density coated modified lithium iron phosphate positive electrode material is obtained.
[0044] According to the present invention, the phosphorus source in step 1 includes phosphate, phosphoric acid or diammonium phosphate, more preferably ferromanganese phosphate and diammonium phosphate; the iron source includes ferric phosphate or iron oxide; the manganese source includes manganese dioxide, manganese carbonate, manganese tetraoxide or ferromanganese phosphate; the lithium source includes lithium phosphate, lithium hydroxide, lithium dihydrogen phosphate or lithium acetate, more preferably lithium carbonate; the titanium source includes titanium oxide, titanium sulfate or titanium chloride, more preferably titanium oxide; the magnesium source includes magnesium nitrate, magnesium chloride, magnesium oxide or magnesium carbonate, more preferably magnesium oxide; the cobalt source includes cobalt oxide, cobalt nitrate, cobalt carbonate, cobalt sulfate, cobalt chloride, cobalt bromide, cobalt phosphate or cobalt hydroxide, more preferably cobalt oxide; the carbon source includes polypyrrole, sucrose, polyethylene glycol, glucose, polyethylene or polyvinyl pyrrolidone, more preferably glucose.
[0045] According to the present invention, the molar ratio of the metal elements of the phosphorus source, iron source, manganese source, magnesium source, titanium source, cobalt source and lithium source in step 1 satisfies the general formula Li a Fe b Mn c Mg d Ti e Co f PO4, wherein 0.9≤a≤1.6, preferably 1.03, 1.04, 1.05 or 1.06; 0.1≤b≤0.9, preferably 0.37, 0.39, 0.40 or 0.42; 0.1≤c≤0.9, preferably 0.58, 0.59 or 0.62; 0.01≤d≤0.4, preferably 0.02, 0.03 or 0.04; 0.01≤e≤0.4, preferably 0.01, 0.02 or 0.03; 0.01≤f≤0.4, preferably 0.01, 0.02 or 0.03; b+c+d+e+f=1, a:(b+c+d+e+f)=(0.8~1.3):1, preferably (1.01-1.06):1.
[0046] According to the present invention, the dispersant in step 1 is one or more selected from polyvinyl pyrrolidone (PVP), polyacrylic acid (PAA), sodium polyacrylate (PAANa), polyacetimide or sodium phosphate, more preferably polyvinyl pyrrolidone. The mass of the dispersant is preferably 0.0001%-10% of the total mass of the ground mixed material, more preferably 0.001%-3.0%.
[0047] According to the present invention, the grinding in step 1 is wet grinding, and the solvents used include but are not limited to deionized water, ethanol, methanol, preferably ethanol, deionized water and mixed solutions thereof; the solid content of the wet grinding is preferably 30-48%, more preferably 38-42%; the grinding media include but are not limited to zirconium balls or agate balls, preferably zirconium balls; the grinding medium filling rate is preferably 80%-90%, more preferably 85%-90%, and the grinding time is preferably 3-6h, more preferably 3-4h.
[0048] According to the present invention, the temperature of the spray drying in step 1 is preferably 100-300°C, more preferably 210-240°C; the primary sintering heating rate is preferably 2-10°C / min, more preferably 3-5°C / min, the primary sintering temperature is preferably 600-850°C, more preferably 700-850°C, the sintering time is preferably 8-18h, more preferably 10h, and the sintering atmosphere is an inert atmosphere.
[0049] According to the present invention, the three-stage grinding in step 2 is divided into coarse grinding, coarse-fine grinding and fine grinding and all are wet grinding, and the solvents used include but are not limited to deionized water, ethanol, methanol, preferably ethanol, deionized water and mixed solutions thereof; the solid content of the wet grinding is preferably 30-48%, more preferably 38-42%. The diameter of the coarse grinding medium is 1.2mm-2.0mm, preferably 1.4-1.6mm, the grinding time of the coarse grinding is preferably 1-5h, more preferably 2-3h, and the sand milling speed is preferably 2000-2600rpm, more preferably 2000-2400rpm; the diameter of the coarse and fine grinding medium is 0.4-1.0mm, preferably 0.4-0.6mm, the grinding time of the coarse and fine grinding is preferably 2-5h, more preferably 3-4h, and the sand milling speed is preferably 2000-2700rpm, more preferably 2400-2600rpm; the diameter of the fine grinding medium is 0.2-0.4mm, preferably 0.2-0.3mm, the grinding time of the fine grinding is preferably 2-5h, more preferably 3-5h, and the sand milling speed is preferably 2200-2800rpm, more preferably 2400-2800rpm; the grinding medium includes but is not limited to agate balls, zirconium balls, etc., preferably zirconium balls.
[0050] According to the present invention, the slurries of different particle sizes in the step 2 are batch mixed and measured by volume ratio, and the sum of the volume ratios of the coarsely ground slurry, the coarsely and finely ground slurry, and the finely ground slurry is 1, wherein the volume ratio of the coarsely ground slurry is 0.1-0.3, preferably 0.1-0.2, the volume ratio of the coarsely and finely ground slurry is 0.2-0.5, preferably 0.2-0.4, and the volume ratio of the finely ground slurry is 0.3-0.9, preferably 0.3-0.8.
[0051] According to the present invention, the spray drying temperature in the step 2 is preferably 100-300°C, more preferably 210-220°C; the secondary sintering heating rate is preferably 2-10°C / min, more preferably 3-5°C / min, the secondary sintering temperature is preferably 600-850°C, more preferably 650-850°C, the sintering time is preferably 7-16h, more preferably 8-10h, and the sintering atmosphere is an inert atmosphere.
[0052] The present invention also provides the use of the high-density coated modified lithium manganese iron phosphate positive electrode material in a lithium ion battery.
[0053] In order to make the technical solutions and advantages of the present invention more clear, the technical solutions of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention.
[0054] Example 1
[0055] Weigh 0.552kg of lithium carbonate, 1.870kg of iron phosphate, 2.119kg of manganese carbonate, 2.016kg of lithium dihydrogen phosphate, 0.278kg of glucose, 12.81g of magnesium oxide additives, 25.19g of titanium dioxide, 25.52g of cobalt tetroxide, 3.45g of dispersant polyvinyl pyrrolidone, and 10.79kg of deionized water, with a solid content of 39%. Mix them evenly in a premixing tank and then sand grind them. The grinding medium is 0.2-0.3mm zirconium balls with a filling rate of 83%. The sand grinding speed is 2600rpm and the sand grinding time is 3.5h.
[0056] After the sand grinding process is completed, spray drying is carried out, the inlet air temperature is 210°C, the feed amount is adjusted to control the outlet air temperature at 108°C, the centrifugal atomizer speed is 21000rpm, and after the spray drying process is completed, a sintering is carried out, the sintering atmosphere is nitrogen or argon inert atmosphere, the heating temperature is 3°C / min, the insulation temperature is 740°C, and the insulation time is 10h. After completing the first sintering, the lithium iron manganese phosphate semi-finished product is prepared.
[0057] Weigh 4.0kg of lithium manganese iron phosphate semi-finished product, 13.6g of tungsten boride, and 6.28kg of deionized water with a solid content of 39%. After mixing evenly, perform three levels of grinding: coarse grinding, coarse and fine grinding, and fine grinding. For coarse grinding, 1.4mm zirconium balls are used, with a filling rate of 80%, a grinding time of 2h, and a sand mill speed of 2400rpm. The slurry after coarse grinding is divided into two parts, which are directly poured into the batch mixing tank according to 15% of the total volume of the slurry, and the remaining 85% of the slurry is subjected to coarse and fine grinding. For coarse and fine grinding, 0.6mm zirconium balls are used, with a filling rate of 82%, a grinding time of 3h, and a sand mill speed of 2400rpm. The slurry after coarse and fine grinding is divided into two parts, which are poured into the batch mixing tank according to 25% of the total volume of the original slurry, and the remaining slurry is finely ground. For fine grinding, 0.3 mm zirconium balls were used, with a filling rate of 85%, a grinding time of 3.5 h, and a sand mill speed of 2500 rpm. After fine grinding, all the slurry was poured into a batch mixing tank, and the speed of the dispersion disk in the batch mixing tank was 600 rpm. After mixing evenly, a secondary spray drying process was performed.
[0058] Secondary spray drying, the air inlet temperature is 200℃, the feed amount is adjusted to control the air outlet temperature to 110℃, the centrifugal atomizer speed is 21000rpm, after the spray drying process is completed, secondary sintering is carried out, the sintering atmosphere is nitrogen or argon inert atmosphere, the heating temperature is 3℃ / min, the insulation temperature is 710℃, and the insulation time is 7h. After the completion of the secondary sintering, it is crushed by air flow and demagnetized by screening to prepare the finished product of lithium manganese iron phosphate, with the structural formula of Li 1.05 Fe 0.39 Mn 0.58 Mg 0.01 Ti 0.01 Co 0.01 PO 4 .
[0059] Example 2
[0060] Weigh 0.552kg of lithium carbonate, 1.871kg of iron phosphate, 2.120kg of manganese carbonate, 2.017kg of lithium dihydrogen phosphate, 0.278kg of glucose, 19.23g of magnesium oxide additives, 12.71g of titanium dioxide, 25.54g of cobalt tetroxide, 3.45g of dispersant polyvinyl pyrrolidone, and 10.79kg of deionized water, with a solid content of 39%. Mix them evenly in a premixing tank and then sand grind them. The grinding medium is 0.2-0.3mm zirconium balls with a filling rate of 83%. The sand grinding speed is 2600rpm and the sand grinding time is 3.5h.
[0061] After the sand grinding process is completed, spray drying is carried out, the inlet air temperature is 210°C, the feed amount is adjusted to control the outlet air temperature at 108°C, the centrifugal atomizer speed is 21000rpm, and after the spray drying process is completed, a sintering is carried out, the sintering atmosphere is nitrogen or argon inert atmosphere, the heating temperature is 3°C / min, the insulation temperature is 740°C, and the insulation time is 10h. After completing the first sintering, the lithium iron manganese phosphate semi-finished product is prepared.
[0062] Weigh 4.0kg of lithium manganese iron phosphate semi-finished product, 13.6g of tungsten boride, and 6.28kg of deionized water with a solid content of 39%. After mixing evenly, perform three levels of grinding: coarse grinding, coarse and fine grinding, and fine grinding. For coarse grinding, 1.4mm zirconium balls are used, with a filling rate of 80%, a grinding time of 2h, and a grinding speed of 2400rpm. The slurry after coarse grinding is divided into two parts, and 10% of the total volume of the slurry is directly poured into the batch mixing tank, and the remaining 90% of the slurry is subjected to coarse and fine grinding. For coarse and fine grinding, 0.6mm zirconium balls are used, with a filling rate of 82%, a grinding time of 3h, and a grinding speed of 2400rpm. The slurry after coarse and fine grinding is divided into two parts, and 30% of the total volume of the original slurry is poured into the batch mixing tank, and the remaining slurry is finely ground. For fine grinding, 0.3 mm zirconium balls were used, with a filling rate of 85%, a grinding time of 3.5 h, and a grinding speed of 2500 rpm. The slurry after fine grinding was all poured into a batch mixing tank, and the speed of the dispersion disk in the batch mixing tank was 600 rpm. After mixing evenly, a secondary spray drying process was performed.
[0063] Secondary spray drying, the air inlet temperature is 200℃, the feed amount is adjusted to control the air outlet temperature to 110℃, the centrifugal atomizer speed is 21000rpm, after the spray drying process is completed, secondary sintering is carried out, the sintering atmosphere is nitrogen or argon inert atmosphere, the heating temperature is 3℃ / min, the insulation temperature is 710℃, and the insulation time is 7h. After the completion of the secondary sintering, it is crushed by air flow and demagnetized by screening to prepare the finished product of lithium manganese iron phosphate, with the structural formula of Li 1.05 Fe 0.39 Mn 0.58 Mg 0.015 Ti 0.005 Co 0.01 PO 4 .
[0064] Example 3
[0065] Weigh 0.552kg of lithium carbonate, 1.868kg of iron phosphate, 2.118kg of manganese carbonate, 2.014kg of lithium dihydrogen phosphate, 0.277kg of glucose, 6.40g of magnesium oxide additives, 38.074g of titanium dioxide, 25.50g of cobalt tetroxide, 3.45g of dispersant polyvinyl pyrrolidone, and 10.79kg of deionized water, with a solid content of 39%. Mix well in a premixing tank and then sand grind. The grinding medium is 0.2-0.3mm zirconium balls with a filling rate of 83%. The sand grinding speed is 2600rpm and the sand grinding time is 3.5h.
[0066] After the sand grinding process is completed, spray drying is carried out, the inlet air temperature is 210°C, the feed amount is adjusted to control the outlet air temperature at 108°C, the centrifugal atomizer speed is 21000rpm, and after the spray drying process is completed, a sintering is carried out, the sintering atmosphere is nitrogen or argon inert atmosphere, the heating temperature is 3°C / min, the insulation temperature is 740°C, and the insulation time is 10h. After completing the first sintering, the lithium iron manganese phosphate semi-finished product is prepared.
[0067] Weigh 4.0kg of lithium manganese iron phosphate semi-finished product, 13.6g of tungsten boride, and 6.28kg of deionized water with a solid content of 39%. After mixing evenly, perform three levels of grinding: coarse grinding, coarse and fine grinding, and fine grinding. For coarse grinding, 1.4mm zirconium balls are used, with a filling rate of 80%, a grinding time of 2h, and a grinding speed of 2400rpm. The slurry after coarse grinding is divided into two parts, which are directly poured into the batch mixing tank according to 20% of the total volume of the slurry, and the remaining 80% of the slurry is subjected to coarse and fine grinding. For coarse and fine grinding, 0.6mm zirconium balls are used, with a filling rate of 82%, a grinding time of 3h, and a grinding speed of 2400rpm. The slurry after coarse and fine grinding is divided into two parts, which are poured into the batch mixing tank according to a volume ratio of 20% of the total volume of the original slurry, and the remaining slurry is finely ground. For fine grinding, 0.3 mm zirconium balls were used, with a filling rate of 85%, a grinding time of 3.5 h, and a grinding speed of 2500 rpm. The slurry after fine grinding was all poured into a batch mixing tank, and the speed of the dispersion disk in the batch mixing tank was 600 rpm. After mixing evenly, a secondary spray drying process was performed.
[0068] Secondary spray drying, the air inlet temperature is 200℃, the feed amount is adjusted to control the air outlet temperature to 110℃, the centrifugal atomizer speed is 21000rpm, after the spray drying process is completed, secondary sintering is carried out, the sintering atmosphere is nitrogen or argon inert atmosphere, the heating temperature is 3℃ / min, the insulation temperature is 710℃, and the insulation time is 7h. After the completion of the secondary sintering, it is crushed by air flow and demagnetized by screening to prepare the finished product of lithium manganese iron phosphate, with the structural formula of Li 1.05 Fe 0.39 Mn 0.58 Mg 0.005 Ti 0.015 Co 0.01 PO 4 .
[0069] Example 4
[0070] Weigh 0.550kg of lithium carbonate, 1.864kg of iron phosphate, 2.112kg of manganese carbonate, 2.009kg of lithium dihydrogen phosphate, 0.277kg of glucose, 9.60g of magnesium oxide additives, 19.04g of titanium dioxide, 38.16g of cobalt tetroxide, 3.45g of dispersant polyvinyl pyrrolidone, and 10.79kg of deionized water, with a solid content of 39%. Mix well in a premixing tank and then sand grind. The grinding medium is 0.2-0.3mm zirconium balls with a filling rate of 83%. The sand grinding speed is 2600rpm and the sand grinding time is 3.5h.
[0071] After the sand grinding process is completed, spray drying is carried out, the inlet air temperature is 210°C, the feed amount is adjusted to control the outlet air temperature at 108°C, the centrifugal atomizer speed is 21000rpm, and after the spray drying process is completed, a sintering is carried out, the sintering atmosphere is nitrogen or argon inert atmosphere, the heating temperature is 3°C / min, the insulation temperature is 740°C, and the insulation time is 10h. After completing the first sintering, the lithium iron manganese phosphate semi-finished product is prepared.
[0072] Weigh 4.0kg of lithium manganese iron phosphate semi-finished product, 13.6g of tungsten boride, and 6.28kg of deionized water with a solid content of 39%. After mixing evenly, perform three levels of grinding: coarse grinding, coarse and fine grinding, and fine grinding. For coarse grinding, 1.4mm zirconium balls are used, with a filling rate of 80%, a grinding time of 2h, and a grinding speed of 2400rpm. The slurry after coarse grinding is divided into two parts, and 20% of the total volume of the slurry is directly poured into the batch mixing tank, and the remaining 80% of the slurry is subjected to coarse and fine grinding. For coarse and fine grinding, 0.6mm zirconium balls are used, with a filling rate of 82%, a grinding time of 3h, and a grinding speed of 2400rpm. The slurry after coarse and fine grinding is divided into two parts, and 30% of the total volume of the original slurry is poured into the batch mixing tank, and the remaining slurry is finely ground. For fine grinding, 0.3 mm zirconium balls were used, with a filling rate of 85%, a grinding time of 3.5 h, and a grinding speed of 2500 rpm. The slurry after fine grinding was all poured into a batch mixing tank, and the speed of the dispersion disk in the batch mixing tank was 600 rpm. After mixing evenly, a secondary spray drying process was performed.
[0073] Secondary spray drying, the air inlet temperature is 200℃, the feed amount is adjusted to control the air outlet temperature to 110℃, the centrifugal atomizer speed is 21000rpm, after the spray drying process is completed, secondary sintering is carried out, the sintering atmosphere is nitrogen or argon inert atmosphere, the heating temperature is 3℃ / min, the insulation temperature is 710℃, and the insulation time is 7h. After the completion of the secondary sintering, it is crushed by air flow and demagnetized by screening to prepare the finished product of lithium manganese iron phosphate, with the structural formula of Li 1.05 Fe 0.39 Mn 0.58 Mg 0.0075 Ti 0.0075 Co 0.015 PO 4 .
[0074] Example 5
[0075] Weigh 0.550kg of lithium carbonate, 1.864kg of iron phosphate, 2.113kg of manganese carbonate, 2.009kg of lithium dihydrogen phosphate, 0.277kg of glucose, 9.60g of magnesium oxide additives, 19.04g of titanium dioxide, 38.16g of cobalt tetroxide, 3.45g of dispersant polyvinyl pyrrolidone, and 10.79kg of deionized water, with a solid content of 39%. Mix well in a premixing tank and then sand grind. The grinding medium is 0.2-0.3mm zirconium balls with a filling rate of 83%. The sand grinding speed is 2600rpm and the sand grinding time is 3.5h.
[0076] After the sand grinding process is completed, spray drying is carried out, the inlet air temperature is 210°C, the feed amount is adjusted to control the outlet air temperature at 108°C, the centrifugal atomizer speed is 21000rpm, and after the spray drying process is completed, a sintering is carried out, the sintering atmosphere is nitrogen or argon inert atmosphere, the heating temperature is 3°C / min, the insulation temperature is 740°C, and the insulation time is 10h. After completing the first sintering, the lithium iron manganese phosphate semi-finished product is prepared.
[0077] Weigh 4.0kg of lithium manganese iron phosphate semi-finished product, 18.4g of tungsten boride, and 6.28kg of deionized water with a solid content of 39%. After mixing evenly, perform three levels of grinding: coarse grinding, coarse and fine grinding, and fine grinding. For coarse grinding, 1.4mm zirconium balls are used, with a filling rate of 80%, a grinding time of 2h, and a grinding speed of 2400rpm. The slurry after coarse grinding is divided into two parts, and 20% of the total volume of the slurry is directly poured into the batch mixing tank, and the remaining 80% of the slurry is subjected to coarse and fine grinding. For coarse and fine grinding, 0.6mm zirconium balls are used, with a filling rate of 82%, a grinding time of 3h, and a grinding speed of 2400rpm. The slurry after coarse and fine grinding is divided into two parts, and 30% of the total volume of the original slurry is poured into the batch mixing tank, and the remaining slurry is finely ground. For fine grinding, 0.3 mm zirconium balls were used, with a filling rate of 85%, a grinding time of 3.5 h, and a grinding speed of 2500 rpm. The slurry after fine grinding was all poured into a batch mixing tank, and the speed of the dispersion disk in the batch mixing tank was 600 rpm. After mixing evenly, a secondary spray drying process was performed.
[0078] Secondary spray drying, the air inlet temperature is 200℃, the feed amount is adjusted to control the air outlet temperature to 110℃, the centrifugal atomizer speed is 21000rpm, after the spray drying process is completed, secondary sintering is carried out, the sintering atmosphere is nitrogen or argon inert atmosphere, the heating temperature is 3℃ / min, the insulation temperature is 710℃, and the insulation time is 7h. After the completion of the secondary sintering, it is crushed by air flow and demagnetized by screening to prepare the finished product of lithium manganese iron phosphate, with the structural formula of Li 1.05 Fe 0.39 Mn 0.58 Mg 0.0075 Ti 0.0075Co 0.015 PO 4。
[0079] Example 6
[0080] Weigh 0.550kg of lithium carbonate, 1.864kg of iron phosphate, 2.113kg of manganese carbonate, 2.009kg of lithium dihydrogen phosphate, 0.277kg of glucose, 9.6g of magnesium oxide additives, 19.04g of titanium dioxide, 38.16g of cobalt tetroxide, 3.45g of dispersant polyvinyl pyrrolidone, and 10.79kg of deionized water, with a solid content of 39%. Mix well in a premixing tank and then sand grind. The grinding medium is 0.2-0.3mm zirconium balls with a filling rate of 83%. The sand grinding speed is 2600rpm and the sand grinding time is 3.5h.
[0081] After the sand grinding process is completed, spray drying is carried out, the inlet air temperature is 210°C, the feed amount is adjusted to control the outlet air temperature at 108°C, the centrifugal atomizer speed is 21000rpm, and after the spray drying process is completed, a sintering is carried out, the sintering atmosphere is nitrogen or argon inert atmosphere, the heating temperature is 3°C / min, the insulation temperature is 740°C, and the insulation time is 10h. After completing the first sintering, the lithium iron manganese phosphate semi-finished product is prepared.
[0082] Weigh 4.0kg of lithium manganese iron phosphate semi-finished product, 24.8g of tungsten boride, and 6.28kg of deionized water with a solid content of 39%. After mixing evenly, perform three levels of grinding: coarse grinding, coarse and fine grinding, and fine grinding. For coarse grinding, 1.4mm zirconium balls are used, with a filling rate of 80%, a grinding time of 2h, and a grinding speed of 2400rpm. The slurry after coarse grinding is divided into two parts, and 20% of the total volume of the slurry is directly poured into the batch mixing tank, and the remaining 80% of the slurry is subjected to coarse and fine grinding. For coarse and fine grinding, 0.6mm zirconium balls are used, with a filling rate of 82%, a grinding time of 3h, and a grinding speed of 2400rpm. The slurry after coarse and fine grinding is divided into two parts, and 30% of the total volume of the original slurry is poured into the batch mixing tank, and the remaining slurry is subjected to fine grinding. For fine grinding, 0.3 mm zirconium balls were used, with a filling rate of 85%, a grinding time of 3.5 h, and a grinding speed of 2500 rpm. The slurry after fine grinding was all poured into a batch mixing tank, and the speed of the dispersion disk in the batch mixing tank was 600 rpm. After mixing evenly, a secondary spray drying process was performed.
[0083] Secondary spray drying, the air inlet temperature is 200℃, the feed amount is adjusted to control the air outlet temperature to 110℃, the centrifugal atomizer speed is 21000rpm, after the spray drying process is completed, secondary sintering is carried out, the sintering atmosphere is nitrogen or argon inert atmosphere, the heating temperature is 3℃ / min, the insulation temperature is 710℃, and the insulation time is 7h. After the completion of the secondary sintering, it is crushed by air flow and demagnetized by screening to prepare the finished product of lithium manganese iron phosphate, with the structural formula of Li 1.05 Fe 0.39 Mn0.58 Mg 0.0075 Ti 0.0075 Co 0.015 PO 4 .
[0084] Comparative Example 1
[0085] Compared with Example 1, the test process of Comparative Example 1 is basically the same, and magnesium oxide, titanium dioxide and cobalt tetroxide are not added in the first sanding process.
[0086] Comparative Example 2
[0087] Compared with Example 2, the test process of Comparative Example 2 is basically the same, and magnesium oxide is not added in the first sanding process.
[0088] Comparative Example 3
[0089] Compared with Example 3, the test process of Comparative Example 3 is basically the same, and titanium dioxide is not added in the first sanding process.
[0090] Comparative Example 4
[0091] Compared with Example 4, the test process of Comparative Example 4 is basically the same, and cobalt tetroxide is not added in the first sanding process.
[0092] Comparative Example 5
[0093] Compared with Example 5, the experimental process of Comparative Example 5 is basically the same, and no tungsten boride additive is added in the third-level grinding process.
[0094] The test results of the synthesis of lithium manganese iron phosphate in the embodiment and the comparative example are shown in the following table:
[0095] serial number Compacted density g / cm3 0.1C discharge capacity mAh / g First lap efficiency% Example 1 2.41 150.8 96.2 Comparative Example 1 2.40 145.8 94.9 Example 2 2.42 151.8 95.4 Comparative Example 2 2.43 150.7 94.6 Example 3 2.45 151.6 96.1 Comparative Example 3 2.44 149.2 94.8 Example 4 2.46 152.5 96.4 Comparative Example 4 2.47 148.2 94.3 Example 5 2.48 154.6 96.5 Comparative Example 5 2.49 148.7 91.2 Example 6 2.49 152.5 95.7
[0096] In the buckle test results, the performance index of Example 5 is the best, which is mainly attributed to the fact that magnesium doping at the Li position can produce cation defects, expand the Li diffusion channel in the lattice structure, and effectively improve the electronic conductivity and lithium ion mobility of lithium manganese iron phosphate. 3+ and Fe 2+ The synergistic effect between 3+ and Fe 2+ Co-doping at the Mn site greatly improves the performance of lithium manganese iron phosphate, thereby improving the dynamic stability of the olivine structure, lithium ion diffusion and electrochemical kinetics; the smaller ion radius of titanium may cause the lattice to shrink along the a, b, and c axes, resulting in a smaller volume and increased surface particle refinement. At the same time, the potential polarization is weakened, and the conductivity of lithium manganese iron phosphate becomes stronger. The charge and discharge curve is shown in Figure 2. Figure 2 As shown, Figure 3In the SEM of Example 5, the single particle size is about 200-300 nm, and particles of different sizes are evenly distributed, so that the powder compaction density is as high as 2.49 g / cm3. This also confirms that three-stage grinding and batch mixing of slurries of different particle sizes can effectively improve the powder compaction density of the material.
[0097] In Example 5, a properly proportioned tungsten boride is coated on the modified lithium manganese iron phosphate positive electrode material to improve the cycle capacity. After the tungsten boride is coated with the lithium manganese iron phosphate, a chemical force is formed on the surface to effectively inhibit the Mn 2+ dissolution, significantly weakening the polarization phenomenon, making the positive electrode material show good long-cycle stability. Figure 4 Cycle trend chart Under 1C high charge and discharge rate cycle conditions, the battery was cycled 100 times with a retention rate of 91.4%.
[0098] It should be understood that the application of the present invention is not limited to the above-mentioned specific embodiments. For ordinary technicians in this field, improvements or changes can be made according to the above description. All these improvements and changes should fall within the scope of protection of the claims attached to the present invention.
Claims
1. A high-density coated modified lithium manganese iron phosphate positive electrode material, characterized in that: including a doped lithium manganese iron phosphate material and a coating layer; The chemical formula of the doped lithium manganese iron phosphate material is Li a Fe b Mn c Mg d Ti e Co f PO4, where 0.9≤a≤1.6, 0.1≤b≤0.9, 0.1≤c≤0.9, 0.01≤d≤0.4, 0.01≤e≤0.4, 0.01≤f≤0.4, b+c+d+e+f=1, a:(b+c+d+e+f)=(0.8~1.3):1; The coating layer is tungsten diboride.
2. The high-density coated modified lithium manganese iron phosphate positive electrode material according to claim 1, characterized in that: The total mass of the high-density coated modified lithium manganese iron phosphate positive electrode material is 100%, the mass content of tungsten diboride in the coating layer is 0.01%-2.0%, and the mass content of the carbon coating is 1%-10%.
3. The method for preparing the high-density coated modified lithium manganese iron phosphate positive electrode material according to claim 1, characterized in that: The steps include: Step 1: uniformly mix the phosphorus source, iron source, manganese source, lithium source, carbon source, titanium source, magnesium source, cobalt source and dispersant, grind, spray dry and perform a sintering to obtain a semi-finished product of lithium manganese iron phosphate; Step 2: The lithium iron phosphate semi-finished product obtained in step 1 is mixed with tungsten boride and sand milling solvent and then subjected to three-stage grinding. The slurries of different particle sizes are batch mixed. After mixing evenly, secondary spray granulation is performed. After secondary sintering, air flow crushing is performed. After screening and demagnetization, a high-density coated modified lithium iron phosphate positive electrode material is obtained.
4. The method for preparing the high-density coated modified lithium manganese iron phosphate positive electrode material according to claim 3, characterized in that: The phosphorus source in step 1 includes phosphate, phosphoric acid or ammonium dihydrogen phosphate; Iron sources include iron phosphate or iron oxide; Manganese sources include manganese dioxide, manganese carbonate, manganese tetraoxide or ferromanganese phosphate; The lithium source includes lithium phosphate, lithium hydroxide, lithium dihydrogen phosphate or lithium acetate; The titanium source includes titanium oxide, titanium sulfate or titanium chloride; Magnesium sources include magnesium nitrate, magnesium chloride, magnesium carbonate or magnesium oxide; The cobalt source includes cobalt oxide, cobalt nitrate, cobalt carbonate, cobalt sulfate, cobalt chloride, cobalt bromide, cobalt phosphate or cobalt hydroxide; Carbon sources include polypyrrole, sucrose, polyethylene glycol, glucose, polyethylene or polyvinyl pyrrolidone.
5. The method for preparing the high-density coated modified lithium manganese iron phosphate positive electrode material according to claim 3, characterized in that: The grinding described in step 1 is wet grinding, and the solvent used includes deionized water, ethanol or methanol. The solid content of the wet grinding is 30-48%, and the grinding medium filling rate is 80%-90%.
6. The method for preparing the high-density coated modified lithium manganese iron phosphate positive electrode material according to claim 3, characterized in that: The spray drying temperature in step 1 is 100-300° C., the primary sintering temperature is 600-850° C., the sintering time is 8-18 hours, and the sintering atmosphere is an inert atmosphere.
7. The method for preparing the high-density coated modified lithium manganese iron phosphate positive electrode material according to claim 3, characterized in that: The three-stage grinding described in step 2 is divided into coarse grinding, coarse and fine grinding, and fine grinding, wherein the diameter of the grinding medium of the coarse grinding is 1.2mm-2.0mm; the diameter of the grinding medium of the coarse and fine grinding is 0.4-1.0mm; the diameter of the grinding medium of the fine grinding is 0.2-0.4mm; Grinding media include agate balls or zirconium balls.
8. The method for preparing the high-density coated modified lithium manganese iron phosphate positive electrode material according to claim 3, characterized in that: The slurries of different particle sizes described in step 2 are batch mixed and measured by volume ratio. The sum of the volume ratios of the coarsely ground slurry, the coarsely and finely ground slurry, and the finely ground slurry is 1, wherein the volume ratio of the coarsely ground slurry is 0.1-0.3, the volume ratio of the coarsely and finely ground slurry is 0.2-0.5, and the volume ratio of the finely ground slurry is 0.3-0.
9.
9. The method for preparing the high-density coated modified lithium manganese iron phosphate positive electrode material according to claim 3, characterized in that: The spray drying temperature in step 2 is 100-300° C., the secondary sintering temperature is 600-850° C., the sintering time is 7-16 hours, and the sintering atmosphere is an inert atmosphere.
10. Use of the high-density coated modified lithium manganese iron phosphate positive electrode material according to claim 1 in lithium-ion batteries.
Citation Information
Patent Citations
Lithium manganese iron phosphate positive electrode material, preparation method thereof and lithium ion battery
CN116812898A
Preparation method of high-conductivity super-ionic conductor composite lithium manganese iron phosphate positive electrode material
CN117049495A
Cited By
Composite positive electrode material and preparation method and application thereof
CN120933325A